[tex]d) \\(1\frac18-\frac12)*(\frac35+\frac13)=(\frac{9}{8}-\frac48)*(\frac9{15}+\frac{5}{15})=\frac58*\frac{14}{15}=\frac{7}{12}[/tex]
[tex]e) \\1\frac15*1\frac23*\frac17+(1\frac17)^2=\frac{6}{5}*\frac53*\frac17+(\frac87)^2=\frac63*\frac17+\frac{64}{49}=2*\frac17+\frac{64}{49}=\frac27+\frac{64}{49}=\frac{14}{49}+\frac{64}{49}=\frac{78}{49}=1\frac{29}{49}[/tex]
[tex]f)\\(2\frac16-\frac23)^2-2\frac15=(\frac{13}{6}-\frac46)^2-\frac{11}{5}=(\frac{9}{6})^2-\frac{11}{5}=(\frac{3}{2})^2-\frac{11}{5}=\frac{9}{4}-\frac{11}{5}=\frac{45}{20}-\frac{44}{20}=\frac1{20}[/tex]
[tex]g)\\10-2*(3\frac15-2\frac14*\frac13)=10-2*(\frac{16}5-\frac{9}4*\frac13)=10-2*(\frac{16}5-\frac34)=10-2*(\frac{64}{20}-\frac{15}{20})=10-2*\frac{49}{20}=10-\frac{49}{10}=\frac{100}{10}-\frac{49}{10}=\frac{51}{10}=5\frac1{10}[/tex]
[tex]h)\\(\frac73-\frac5{12}+1\frac12):(2\frac34-\frac56)=(\frac73-\frac{23}{12}):(\frac{23}{12})=\frac5{12}*\frac{12}{23}=\frac5{23}[/tex]